The Perception of Plastic Surgery by Community-Based, Private Practice Nurses: A French National Descriptive Study. Issue 1 (January 2021) - Lupon, Elise; Girard, Paul; Lupon, Amélie; Jacques, Loriane; Jung, Ludivine; Ng, Zhi Yang; Lantieri, Laurent Alexandre; Laloze, Jérôme; Lellouch, Alexandre Gaston
Abstract : Plastic surgery is a dynamic field but remains poorly understood by general practitioners, medical students, health professionals, and the public. The main health care professionals in the community who are involved in the follow-up of plastic surgery patients are nurses; they help to facilitate wound healing and rehabilitation in the postoperative period. In this study, the authors assessed the medical knowledge and perceptions of plastic surgery by nurses working in the community setting and explored their understanding of classical scenarios commonly encountered in reconstructive surgery. An online survey was designed to assess the demographics of nurses working in the community in France and their knowledge of plastic surgery. This was disseminated to all practicing nurses working outside of hospitals by means of an online social network from the period of April 2019 to June 2019. The survey was completed by 318 nurses. Specific training in plastic surgical nursing will be required to optimize the management of these patients following discharge from hospital. This gap in knowledge may affect patient recovery negatively.